Film Festivals Jury Committees and Quality Cinema : Case study of the San Sebastian International Film Festival - Jurado-Martín, Montserrat (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
In whose hands do we trust to determine what quality cinema is? Based on this premise, the jury committee of the San Sebastian Film Festival is analyzed, as responsible for determining which the best productions are. The methodology used is the analysis of the content of its website and a sample of 24 people in the 2021 edition. The conclusions will show that there are more women than men, with higher university studies, active in film production and with little experience as jurors. The analysis leaves the door open for debate on the composition of these committees.